Upaya Pencegahan dan Penanganan Stunting dengan Pengenalan Program Siganting Melalui Kader Di Kota Surakarta - Sukamto, Ika Sumiyarsi; Argaheni, Niken Bayu; Juwita, Septiana (Universitas Sebelas Maret, 2023)
Introduction: Stunting, a condition where toddlers have a height significantly below the normal for their age, remains a serious issue in Indonesia, including the city of Surakarta. This has serious implications for a child's physical and cognitive development. Factors contributing to stunting are divided into direct factors (maternal nutrition, feeding practices, exclusive breastfeeding) and indirect factors (healthcare, education, environmental sanitation). Addressing stunting requires the involvement of healthcare professionals and community health volunteers. Effective training is crucial to enable kader to play a significant role in this effort.Method: This community engagement introduces the Siganting Program, a mobile application designed for stunting prevention. The program was presented to healthcare professionals and kader in Surakarta through lectures and discussions. Pre- and post-tests were used to assess participants' understanding of the program.Results: The Siganting Program successfully increased participants' understanding of stunting prevention. Before the program introduction, the average pre-test score was 76.4%, while the post-test showed 100% comprehension among participants.Conclusion: The Siganting Program is a valuable tool for stunting prevention and management, especially for mothers with infants under two years old. It can help Surakarta move closer to its goal of reducing stunting prevalence to zero. This mobile application provides accessible and flexible support for mothers and has been well-received by healthcare professionals and kader. The use of technology like Siganting can assist in achieving a significant reduction in stunting rates in Surakarta and its surrounding areas.